Recognition of Human Emotions Using Advanced Deep Neural Networks - Aruna, D.Devi; Kumuthini, C.; Ramya, B.; Kumar, P.Dinesh (Journal of Neonatal Surgery, 2025)
Human emotion recognition systems have become an important component in various fields such as healthcare, education, security and mainly in human-computer interaction. Facial emotions are a form of nonverbal communication a person may use that provides additional meaning to verbal communication. An efficient system is required to understand these emotions and use them in further decisions and research. This paper is based on a system that is able to detect human emotions in real time using real cameras. This system integrates deep learning models with computer vision, which extracts unique features from the data provided to detect emotions in real time and also understand and respond to emotions accordingly.